EVALUASI PENYULUHAN PEMILAHAN SAMPAH ORGANIK DAN ANORGANIK PADA SISWA BERKEBUTUHAN KHUSUS, PENDIDIKAN USIA DINI SEKOLAH LUAR BIASA BALI - Imroatul Ippah; Husnayaen Husnayaen; Riyani Bela; Azizah Azis; Suci Rahmawati; Adrian Pratama Putra (Universitas Mataram, 2026)
Bali is one of the most famous destinations in the world and trash will always be one of the problems. Since few years back Bali goverment intense education to the local society about waste management, especially the separation between organic and inorganic trash. Even though waste management education is not easy for the special needs early education student because of some reason such as facility limitation, the student understanding and the integration between education implementation with the environmental education is not optimal. Therefore, as a community service from the Institute of Science and Technology Nahdlatul Ulama Bali (ISTNUBA) tried to deliver education for the special needs children in the Special Need School No 1 Denpasar. The aims of this activity are to make the student understand more about organic and inorganic waste, to give an evaluation for the activity whether it is effective or not and to get suggestions for future activities. The methods are explaining in small student groups and practice as a game. The result is the method effective for the early education special needs student. The higest suggestions is after waste separation management.